The impact of the Mental Health Act No. 18 of 1973 and related legislation on sentencing practices at the Cape Town Supreme Court, 1964-1980 - Kruger, Wilanda (Stellenbosch : Stellenbosch University, 2020)
Thesis (MA)--Stellenbosch University, 2020.